Hold paramount the engineer's responsibility to society - Vesilind, P. Aarne; Gunn, Alastair S. (Cencage Learning, 2016)
Covers ethical dilemmas that any engineer might encounter on the job, emphasizing the responsibility of a practicing engineer to act in an ethical manner. To illustrate the complexities involved, the authors present characters who encounter situations that test the engineering code of ethics